Characterization of SUMO proteases and other proteins involved in water stress responses in Triticum aestivum L. - Le Roux, Marlon-Schylor (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhDAgric)--Stellenbosch University, 2021.